The Role of Telemedicine in the Treatment of Cognitive and Psychological Disorders in Parkinson’s Disease: An Overview - Desirèe Latella; Giuseppa Maresca; Caterina Formica; Chiara Sorbera; Amelia Bringandì; Giuseppe Di Lorenzo; Angelo Quartarone; Silvia Marino (Brain Sciences, 2023)
Background: This literature review evaluates the use and efficacy of telemedicine in cognitive and psychological treatment in Parkinson’s disease. Methods: Studies performed between 2016 and 2021 that fulfilled inclusion criteria were selected from PubMed, Scopus, Cochrane, and Web of Science databases. All articles were evaluated by title, abstract, and text. All studies that examined the cognitive and psychological/psychotherapy treatment of patients with Parkinson’s disease by telemedicine were included. Results: Telehealth improved cognitive status and emotional/behavioral disorders in this population, and had positive effects on the patients’ and caregivers’ quality of life. Conclusions: Our literature review supports the development and efficacy of cognitive and psychological treatment with telemedicine, but the methodology of the study must be reviewed considering its limitations so as to highlight the benefits and risks of treatment via telemedicine.